A new Track of Fatigue crack growth in Aluminum Alloy (2219) under Cyclic Stresses - Abdullah Dhayea Assi (Journal of Techniques)
A study of new Track of Fatigue crack growth in aluminum alloy (2219) under cyclic stresses has been made. It was found out that this crack grow and propagate in three phases, the first phase though the grain size (micro-structure short cracks(MSC)), second phase cross the boundary of the grain size to about 1mm in length (physically short cracks (PSC)) and the third phase up to the final fracture (Length cracks(LC)).  In addition, two programs were designed on MATLAB to perform the compute calculations to collect the results. The first program to calculate the practical constants and the second to make the calculations required to complete the work schedules. The stress and the parameters effecting the growth of these cracks in each phase were studied. A model consisting of three formulas was established from the experimental results. Each formula describes the behavior of the cracks in the particular phase. The comparison showed that the proposed model is safer than the experimental results for the designed parts of aircraft.